DARI ATAS KE BAWAH: DIMENSI YURIDIS TANGGUNG JAWAB PEMIMPIN MILITER ATAS PELANGGARAN PASUKAN - Andi Ichsan; Educ Permadi Eko, Tarsisius Susilo, Dinand Tumpak, Wahyu Ramadhanus (INTELIGENSIA MEDIA, 2025)
The enforcement of international humanitarian law (IHL) in domestic conflicts often intersects with the issue of state sovereignty, particularly when involving the intervention of international actors. This article explores the dynamics of international organizations—such as the International Committee of the Red Cross (ICRC), the United Nations (UN), and global non-governmental organizations (NGOs)—in two critical conflict areas in Indonesia: the armed conflict and subsequent secession of East Timor, and the protracted unrest in Papua. Employing a juridical-critical and historical-qualitative approach, this study systematically distinguishes between the official mandates of these organizations and their actual field operations, which at times have extended beyond the principle of neutrality and influenced the integrity of Indonesia’s national sovereignty. The findings indicate that while certain organizations, such as the ICRC, largely adhered to their humanitarian mandates, others—including the UN and prominent human rights NGOs—played a politically significant role, particularly in facilitating East Timor’s separation from Indonesia. In contrast, international involvement in Papua has been more limited yet continues to exert global pressure through human rights advocacy. Indonesia's defensive yet progressive response has proven effective in preserving sovereignty in Papua, drawing lessons from the East Timor experience. The article recommends a selective synergy between international cooperation and the safeguarding of non-intervention principles, ensuring that the enforcement of humanitarian law is not exploited as a political instrument by foreign entities